Virtual piano instruction for the college learner - Gena Greher; Dominique Haughton; Jacob Hiser; Brandon Vaccaro (Journal of the Association for Technology in Music Instruction, 2021)
This article investigates the affordability and feasibility of conducting virtual piano lessons for the college level learner. It proposes an approach that works well and requires equipment costing approximately $300 per student. We outline the pros and cons of conducting virtual piano lessons online. The main benefit is overcoming geographical distances, whereas limitations include challenges such as the instructor being able to check issues such as fingerings or dynamics. Latency is not a major problem as long as only one person is playing at any given time, as found in past work. The process of teaching and learning online requires the student to be strongly motivated, and it is helpful for instructor and student to have worked together before in non-virtual environments.
Keywords: Virtual piano instruction; college piano learner; Skype; Zoom; latency; Jamulus